Effects of Dietary Fiber Intake on Body Weight and Waist Circumference - Al Hammadi, Eiman (Arab Journal of Nutrition and Exercise (AJNE), 2017)
Aim: Obesity levels dramatically increased in the last decade in UAE. Diets high in energy, saturated fatty acids, low intake of fruits and vegetables as well as inactivity have been found to promote overweight and obesity. A diet high in fiber has been suggested to improve weight loss and decrease other anthropometrical indices. The purpose of this study was to assess the effect of a diet high in fiber on body weight, BMI, and waist circumference (WC). Methods: One hundred forty overweight/obese subjects aged from 20-30 years old participated in the study. Body weight (BW), body mass index (BMI) and waist circumference (WC) was measured after one month period in which the subjects consumed diet high in dietary fiber (38 g/d/men, 25 g/d/women). SPSS was used for the analysis of data and statistically significant difference was set at P> 0.05. Results: BW, BMI and WC were clinically reduced before and after intervention in both males and females. However, these changes were not statistically significant. Percent changes on BW for female and male subjects were 1.45 (95%CI: -12.68, 15.58), P>0.05 and 1.12 (95% CI: -13.58, 15.82), P>0.05, respectively. Conclusion: The high fiber diet did not significantly reduce body weight and WC. Even though there was a small clinically reduction on BW, BMI and WC, however this was not statistically significant. The results, even though were not supportive, they should not discourage people from consuming foods high in fiber, due to other beneficial effects in their health such as decreasing the risk of cancer, lipidemia, type 2 diabetes and metabolic syndrome.